Pengaruh Metode Mind Mapping Terhadap Pembelajaran Maharah Qiroah Mahasiswa Pendidikan Bahasa Arab Universitas Negeri Malang - Fadiyah, Nia Zahrotul; Ma'sum, Ali (Prosiding Konferensi Nasional Bahasa Arab, 2024)
This study aims to determine the impact of the mind mapping method on the learning of Reading Skills for Arabic Language Education students at Universitas Negeri Malang. The object used in this research is the offering A of Arabic Language Education at Universitas Negeri Malang. Data collection techniques involve observation. The results of this study indicate that there are two impacts: positive and negative, of implementing the mind mapping method on the learning of Reading Skills for Arabic Language Education students at Universitas Negeri Malang. Therefore, it can be concluded that the use of the mind mapping method is suitable for implementation in Reading Skills learning.يهدف هذا البحث إلى تحديد أثر طريقة الخريطة الذهنية في تعلم مهارة قراءة من طلاب تعليم اللغة العربية في جامعة مالانج الحكومية. الهدف المستخدم في هذا البحث هو عرض تعليم اللغة العربية، طلاب في الفصل أ بجامعة مالانج الحكومية. تقنية جمع البيانات هي عن طريق إجراء الملاحظات. أظهرت نتائج هذا البحث أن هناك تأثيرين، تأثير إيجابي وتأثير سلبي لتطبيق طريقة الخريطة الذهنية على تعلم مهارة القراءة لدى طلاب تعليم اللغة العربية في جامعة مالانج الحكومية. ومن هنا يمكن الاستنتاج أن استخدام طريقة الخريطة الذهنية مناسب للتطبيق في تعلم مهارة القراءة.